Environmental filtering and competitive exclusion drive biodiversity‐invasibility relationships in shallow lake plant communities. (6th April 2018) - Muthukrishnan, Ranjan; Hansel‐Welch, Nicole; Larkin, Daniel J.
Abstract: Understanding the processes that influence the diversity of ecological communities and their susceptibility to invasion by exotic species remains a challenge in ecology. In many systems, a positive relationship between the richness of native species and exotic species has been observed at larger spatial (e.g., regional) scales, while a negative pattern has been observed at local (e.g., plot) scales. These patterns are widely attributed to (1) biotic interactions, particularly biotic resistance, limiting invasions in high‐diversity locations, producing negative local‐scale relationships, and (2) native and exotic richness covarying at larger spatial scales as a function of environmental conditions and heterogeneity, producing positive large‐scale relationships. However, alternative processes can produce similar patterns and need to be critically evaluated to make sound inferences about underlying mechanisms. We aggregated a large dataset of aquatic vegetation surveys from 1, 102 Minnesota shallow lakes collected over 13 years to quantify spatial and temporal patterns of community composition. Using those data and additional information on environmental conditions we evaluated evidence for four distinct mechanisms that could drive patterns of native and exotic species richness: biotic resistance, competitive exclusion, environmental filtering and environmental heterogeneity. We found the classic pattern of a negative native‐exotic richness relationship at local scales and a positive relationship at lake scales. However, we found no evidence for local‐scale biotic resistance; instead, competitive exclusion by invasive species appeared to reduce native species richness after locations became invaded. Evaluating the influence of environmental filtering and heterogeneity, we found that native and exotic species occupied somewhat different niches. Invaders were less sensitive to environmental gradients and more tolerant of a wider range of conditions. This segregation of habitat preferences alone could produce a negative local native‐exotic richness relationship and a positive regional pattern without the involvement of biotic interactions. Synthesis . Our findings conflict with established expectations, which come from research predominantly conducted in terrestrial ecosystems. This illustrates the importance of explicitly evaluating underlying mechanisms in diversity‐invasibility research and for comparisons across different types of ecosystems. Identification of different drivers of diversity also has direct implications for decisions about management of freshwater plant communities. Abstract : A variety of processes can influence native‐exotic richness relationships at either the local or regional scale. Other research has led to the expectation that biotic interactions, and biotic resistance in particular, dominate at local scales driving a negative NERR, but that environmental factors play the main role in determining community composition at regional scales producing a positive NERR. Counter to those expectations we found no evidence that biotic resistance had a significant effect at the local scale in lake plant communities, but similar patterns could be produced by competitive exclusion or environmental filtering. However, we did find that environmental factors, via environmental filtering and heterogeneity, dominated at the regional scale.